2020
DOI: 10.1002/essoar.10502714.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mosquito, the Virus, the Climate: An Unforeseen Réunion in 2018

Abstract: The 2018 outbreak of dengue in the French overseas department of Réunion was unprecedented in size and spread across the island. This research focuses on the cause of the outbreak, asserting that climate played a large role in the proliferation of the Aedes albopictus mosquitoes, which transmitted the disease, and led to the dengue outbreak in early 2018. A stage-structured model was run using observed temperature and rainfall data to simulate the life cycle and abundance of the Ae. albopictus mosquito. Furthe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The first two models consist of vectorial capacity models including basic vector to human interactions coupled with stage-structured datadriven dynamic models to describe the population dynamics of Ae aegypti (UMEÅ-aegypti) and Ae albopictus (UMEÅ-albopictus). [27][28][29] These models account for the effects of daily temperature, precipitation, and daylight length in the ecological processes of mosquito populations and for the spatiotemporal dynamics of mosquito populations. The statistical dengue model (DGM) is a generalised additive mixed model that simulates dengue incidence as a function of temperature, precipitation, relative humidity, and population density.…”
Section: Dengue Disease Modelsmentioning
confidence: 99%
“…The first two models consist of vectorial capacity models including basic vector to human interactions coupled with stage-structured datadriven dynamic models to describe the population dynamics of Ae aegypti (UMEÅ-aegypti) and Ae albopictus (UMEÅ-albopictus). [27][28][29] These models account for the effects of daily temperature, precipitation, and daylight length in the ecological processes of mosquito populations and for the spatiotemporal dynamics of mosquito populations. The statistical dengue model (DGM) is a generalised additive mixed model that simulates dengue incidence as a function of temperature, precipitation, relative humidity, and population density.…”
Section: Dengue Disease Modelsmentioning
confidence: 99%
“…This indicator uses a mechanistic model to estimate the basic reproduction rate ( R 0 ) and length of transmission season for dengue combining information on temperature, rainfall, mosquito abundance, and human population density. 48 , 49 Overall, in the period 1986–2020, ( R 0 ) has increased by 17·3% in Europe compared with 1951–1985 ( figure 3B ). This pattern is also observed for chikungunya and Zika virus.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitiesmentioning
confidence: 99%
“…A modelling study in Réunion established a positive association between weather variables and Breteau index using a process-based modelling approach and evaluated the capacity of the climate information in predicting Aedes vector activities with a lead time up to 4 weeks. 38 A study in the Gampaha, Western Province, Sri Lanka, using data for 1 year, found a statistically significant increase only for ovitrap index and not for the vector indices during the two monsoonal periods. 39 Similarly, a study in Hong Kong showed that ovitrap indices were positively correlated with the mean air temperature with a lag up to 22 days and total rainfall with a lag up to 15 days before the ovitrap measurement.…”
Section: Discussionmentioning
confidence: 99%